The Correlation of Fast Food Intake, Breakfast Habits, Vegetable and Fruit Intake, Physical Activity, and Nutritional Status in Students of SMP Negeri 7 Jambi City - Suzan, Raihanah; Amini, Afifah; Siregar, Mara Imam Taufiq (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
Background: Based on the 2018 Riskesdas in Jambi Province, the prevalence of obesity in the 13-15 year age group was 8.13%. Data from the Jambi City Health Office from 2016 to 2018 showed that cases of obesity consistently increased every year. This study aimed to determine the relationship between fast food intake, breakfast habits, vegetable and fruit intake, physical activity, and nutritional status in SMP Negeri 7 Jambi students, Methods: This research is a categorical comparative analytic observational study with a cross-sectional approach. Data were obtained by anthropometric examination; intake of fast food, vegetables, and fruit was obtained from the FFQ, data on breakfast habits were obtained from a questionnaire, and physical activity data were obtained from the IPAQ questionnaire, Results: Most of the 101 respondents were aged 13 years (41.6%), male-dominated by gender (52.5%), and the majority of them were norm weight (54.5%). The frequency of fast food intake is mainly classified as rare, and the type often consumed is chicken nuggets (31.7%). The majority of students never breakfast (33.4%). Most of the respondents rarely consumed vegetables and fruit, and the types of vegetables and fruit that were often consumed were oranges (27.7%) and spinach (24%). Most students have moderate physical activity (48.5%). The results of statistical analysis of fast food (p-value 0.001), breakfast habits (p-value 0.002), physical activity (p-value 0.001), and nutritional status have a significant relationship. In contrast, vegetables and fruit and nutritional status do not have a significant relationship (p-value 0.441), Conclusion: There is a significant relationship between fast food, breakfast habits, and physical activity with nutritional status, and no significant relationship is found between vegetables and fruit and nutritional status. Keywords: Nutritional status, fast food, breakfast habits, vegetables and fruits, physical activity